PROTES SOSIAL DALAM NOVEL PULANG KARYA LEILA S. CHUDORI: PENDEKATAN SOSIOLOGI SASTRA - Peka Tariska; Widowati Widowati (CARAKA, 2018)
The aims of the research are to describe these subjects. (1) Facts story from the novel Pulang; (a) plot, (b) characters and characterization, (3) The sttinngs which used by the author to show socialogical probtem in the novel. (4) CiviliansÂ  pitcrures inÂ  theÂ  novelÂ  â€œPulangâ€. (5) Social protest in the novel Â Pulang.Â  This rescarchÂ  isÂ  oneÂ  of the descriptiv ,qualitativeÂ  rescarchâ€™sÂ  kind . Data used in the from of sentecesÂ  and pragrahs.Â  TheseÂ  dataÂ Â  areÂ  obtainedÂ Â  fromÂ  theÂ  secondÂ  colitionÂ Â  ofÂ  theÂ  novel â€œPulangâ€Â  byÂ  LeilaÂ  S . Chundori.Â  The instruments ofÂ  thisÂ  researchÂ  isÂ  theÂ  researsherÂ Â  herselfÂ Â  withÂ  severalÂ  theoriesÂ  ofÂ  intrinsic andÂ  literatureâ€˜sÂ  socialogical asÂ  theÂ  knifeÂ  ofÂ  analysis.Â  TheÂ  method and techniques of data collection used in this study are non-interactive and reading and note techniques.Â  The method and techniques of data analysis in this research is descriptive method and descriptive analysis. The resultsÂ  ofÂ  thisÂ  researchÂ Â  areÂ Â  asÂ Â  follows. (1) Facts story from the novel â€œPulangâ€; (a) showingÂ  thatÂ  the authorÂ  appliedÂ  a flashbackÂ  plot, (b) charactersÂ  andÂ Â  characterizationsÂ  from the novelÂ  â€œPulangâ€Â  areÂ  composed of one main character and four additional characterÂ  with a simple gesture, Â (c)Â  theÂ  settingÂ  inÂ  thisÂ  novelÂ  areÂ  tateingÂ  placeÂ  fromÂ  someÂ  citiesÂ  ofÂ  differentÂ  countrry. byÂ  usingÂ  timeÂ  intervalÂ  onÂ  1998â€™sÂ Â  social incident. (4)Â  PicturesÂ  ofÂ  theÂ  societyÂ  capturedÂ  inÂ  this novelÂ Â  areÂ  fromÂ  exiledÂ  families,Â  politicalÂ  families,Â  theirÂ Â  limitnessÂ  fromÂ  someÂ  accessÂ  inÂ  theÂ  countryÂ  andÂ Â  their love to theirÂ  nation. (5) The kind of social protest shown in the novel â€œPulangâ€ is a social-politics protest for the rulerÂ  andÂ  social- politicÂ  protestÂ  for society.